1999
DOI: 10.1007/bf02345565
|View full text |Cite
|
Sign up to set email alerts
|

INAA of Aegaean pumices for the classification of archaeological findings

Abstract: Instrumental neutron activation analysis (1NAA) was used to determine 29 elements in pumice from several volcanic sources (Milos, Nisyros, Yali, Kos and Thera) in the Aegean Sea, Greece, to establish a data basis for the identification of pumice and tephra layers found in archaeological context. The widespread products of the "Minoan Eruption" of the Thera volcano can now be distinguished clearly from all other sources and will be used to establish a datumline in the Eastern Mediterranean Region in the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…The pronounced negative Eu anomaly is attributed to the plagioclase fractionation which is normally expected in such highly evolved lavas. In contrast to these results, the element concentrations in the bulk material and the glass phase of pumice from other sources, for example from the island Kos, show more signi®cant differences due to their higher content of mineral phases [15]. Work is in progress on the latter question and the separation techniques developed are being applied to pumice from different primary sources in the Aegean.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The pronounced negative Eu anomaly is attributed to the plagioclase fractionation which is normally expected in such highly evolved lavas. In contrast to these results, the element concentrations in the bulk material and the glass phase of pumice from other sources, for example from the island Kos, show more signi®cant differences due to their higher content of mineral phases [15]. Work is in progress on the latter question and the separation techniques developed are being applied to pumice from different primary sources in the Aegean.…”
Section: Resultsmentioning
confidence: 83%
“…Nevertheless, previous work has shown that the composition of the pure pumice fraction varies only within a very narrow range [14,15]. Only the ®rst layer (Bo1), which is related to the Plinian phase of the eruption, is of interest for this investigation.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Their geographical locations are shown in Figure 4.1, a sample overview is given in Table 4.1. The sample preparation is described in detail in Peltz et al (1999). The analytical results allow a clear identification of the volcanic sources (Bichler 88 Otto Cichocki et al 4.5 show the natural variation ranges of these Aegean pumice sources and the agreement with some typical samples from excavations.…”
Section: Pumice Resultsmentioning
confidence: 99%
“…Furthermore, pumice is a very useful abrasive and has been collected and traded since prehistoric times, as reported by Pliny in his Natural History book XXXVI (Faure 1971). The applicability for chronological purposes has been checked in earlier studies by demonstrating that the "Minoan" pumice is sufficiently homogeneous and can be distinguished from the numerous other Aegean pumice sources by its trace element distribution pattern ("chemical fingerprinting"; Bichler et al 1997;Peltz et al 1999;Schmid et al 2000). The identification of distant tephra layers and the possible sources of errors are discussed in Schmid et al (2000) and Saminger et al (2000).…”
Section: The Thera Ashes Projectmentioning
confidence: 99%
“…Smaller pumice deposits found on the western part of Kimolos Island thin towards Milos Island to the southwest. However, there are other pumice fragment deposits along the coastlines of the southern Aegean in Milos, Anafi, and Crete islands [9][10][11][12][13][14][15]. These are not associated with local volcanic activity, and may represent flotation deposits.…”
Section: Introductionmentioning
confidence: 99%